ANALISIS NILAI MORAL LAGU DAERAH DALAM MEMBENTUK KEDISIPLINAN SISWA DONGENG - Sovi Fariha Anif; Husni Wakhyudin; Wawan Priyanto (Jurnal Lensa Pendas, 2019)
This study aims to determine the moral values contained in regional songs in shaping the discipline of fifth grade students of Mangunharjo Elementary School Semarang. This type of research is qualitative with descriptive method. Sources of data in this study are moral values and observations of student discipline, questionnaires and interviews with teachers. Data in this study were collected by observation, interviews, questionnaires and documentation. Based on the results of research observations found that undisciplined behavior by fifth grade students at Mangunharjo Public Elementary School, among others, did not use uniforms according to school regulations, eating when learning took place, not doing assignments. The results show that there are moral values of religiousity, responsibility, gender, and sociality in the gundul-gundul pacul, and padang bulan songs. The song is used by the teacher as an effort to discipline students. The results of the use of folk songs that have been made indicate that the gundul-gundul pacul and padang bulan regional songs can be used as one of the media that can change students' disciplinary behavior in accordance with the given stimulus.